Plants and phytochemicals for Huntington’s disease - Choudhary, Sunayna; Kumar, Puneet; Malik, Jai (Pharmacognosy Reviews, 2013)
Huntington’s disease (HD) is a neurodegenerative disorder characterized by progressive motor dysfunction, including chorea and dystonia, emotional disturbances, memory, and weight loss. The medium spiny neurons of striatum and cortex are mainly effected in HD. Various hypotheses, including molecular genetics, oxidative stress, excitotoxicity, metabolic dysfunction, and mitochondrial impairment have been proposed to explain the pathogenesis of neuronal dysfunction and cell death. Despite no treatment is available to fully stop the progression of the disease, there are treatments available to help control the chorea. The present review deals with brief pathophysiology of the disease, plants and phytochemicals that have shown beneficial effects against HD like symptoms. The literature for the current review was collected using various databases such as Science direct, Pubmed, Scopus, Sci‑finder, Google Scholar, and Cochrane database with a defined search strategy.
Keywords: Brahmi; Celastrol; Ginkgo biloba; Sesamol; Withania somnifera